Comparison of 0.5% Ropivacaine with 0.5% Ropivacaine and Magnesium sulphate in supraclavicular brachial plexus block for forelimb and hand surgeries - Taneja, Parvez; Singh, Manjit; Singh, Balwinderjit; Pal Attri, Joginder (International Journal of Medical Research and Review, 2018)
Objectives: Supraclavicular Brachial Plexus is commonly used for forelimb and hand surgeries. A lot of research is going on to increase the duration of sensory and motor blockade by the addition of adjuvants with the local anesthetics. We evaluated the effect of adding magnesium sulphate to ropivacaine for supraclavicular brachial plexus blockade. Our primary parameters were the onset and duration of sensory and motor block and duration of analgesia. Methods: 60 patients posted for elective forearm and hand surgeries under supraclavicular brachial plexus block were divided into two equal groups (Group RM and RN) in a double blind fashion. In Group RM 30ml 0.5% ropivacaine plus 150 mg magnesium sulphate in (1 ml 0.9% saline) and in group RN 1ml of normal saline was added to ropivacaine. Results: Both the groups have similar demographic profile and time of onset of senory and motor block but the duration of senory and motor blockade and duration of analgesia were significantly longer in RM group than RN group. Intraoperative hemodynamics were compareable amoung two groups and no considerable side effects were noted in both the groups. Conclusion: It can be concluded from our study that by addition of magnesium sulphate to local anesthetics in supraclavicular brachial plexus block may increase the duration of senory and motor blockade and duration of analgesia with no appreciable side effects, however duration of onset of sensory and motor blockade was more in magnesium sulphate group.